THE MEAN PRE AND POST OP HEMOGLOBIN LEVEL IN PATIENTS IN CASE WITH BLOOD LOSS UNDERGOING CAESARIAN SECTION DEPARTMENT OF GYNECOLOGY AND OBSTETRICS SAIDU GROUP OF TEACHING HOSPITAL SWAT (The Research of Medical Science Review, 2025)
Background: Obstetric hemorrhage can cause severe complication but it could be preventable. A key factor in lowering mortality and morbidity associated with C-sections is the early detection of blood loss and timely management. The mean pre and post-op hemoglobin level is an indicator of blood loss in patients undergoing Caesarian section.Methodology: It was a Quasi Experimental study, conducted in department of Gynecology and Obstetrics Saidu Group of teaching Hospital (SGTH) Swat. It was a six-month study and data collection were started after the approval from CPSP Pakistan. Sample size was calculated using open epi.com software Data was collected using Written proforma through non-probability sampling technique.Results: The study of 60 patients (mean age 28.54 ± 1.32 years) found mean operation time was 44.08 ± 7.91 minutes and mean intraoperative blood loss was 660 ± 86 ml, with no significant differences between age groups. Mean pre- and post-operative hemoglobin levels were 11.59 ± 1.01 g/dl and 9.85 ± 0.14 g/dl, respectively (paired t-test p = 0.0003). There was a significant negative correlation between intraoperative blood loss and drop in post-op hemoglobin (r = -0.45, p < 0.05).Conclusion: Our study concludes that older patients (34-40 years) tended to have higher blood loss and lower postoperative hemoglobin levels (9.85±0.14 g/dl) compared to younger groups. Overall hemoglobin drop (1.74 g/dl) after C-section was clinically significant, showing a direct relationship between increased blood loss and lower postoperative hemoglobin levels. The findings suggest age may influence surgical outcomes, but larger studies are needed to confirm these trends.